Rhetorical Structures of English-Major Undergraduate Thesis Introduction Chapters - Ruth Dewi Indrian; Priyatno Ardi (Indonesian Journal of EFL and Linguistics, 2019)
Undergraduate students are required to write a thesis to obtain a degree. One of the most important chapters in the thesis is introduction. Introduction section plays an important role because it describes what the research is all about. To write an introduction chapter, Swales (1990) proposed Create-a-Research-Space (CARS) model, which include three moves, namely establishing a territory, establishing a niche, and occupying the niche. Every move consists of several steps. This study aims to analyze Swales’ CARS model in the introduction chapters of undergraduate theses written by English major students. Furthermore, the lexical and syntactical signals in each move and step are investigated. This research employed discourse analysis, which focuses on how texts are structured. The researchers analyzed 18 introduction chapters of undergraduate theses written by the English major students of Sanata Dharma University who graduated in 2017. In analyzing the corpus, the researcher used top-down analysis. The results showed that Move 1, Establishing a territory, appeared in the undergraduate theses. However, many of the students did not review the previous research. Move 2, Establishing a niche, was presented in three theses. In this stage, many of the students did not fill in the gap about the previous research. Move 3, Occupying the niche, was frequently used by the students. In this phase, the students outlined the purpose of their research. This study also found that the lexical and syntactical signals used in the theses were quite different from Swales’ CARS model.